Coupled flow and geomechanical analysis for gas production from marine heterogeneous hydrate-bearing sediments. (15th September 2022) - Dong, Bao-Can; Xiao, Peng; Sun, Yi-Fei; Kan, Jing-Yu; Yang, Ming-Ke; Peng, Xiao-Wan; Sun, Chang-Yu; Chen, Guang-Jin
Abstract: For natural gas hydrate exploitation, revealing the interaction between flow and geomechanics is the key to accurate prediction of gas production and formation stability. In this work, based on the site GMGS3-W19 of the South China Sea, a numerical model with multilayer hydrate deposits was established to analyze the evolution of geological parameters during depressurization. The results demonstrated that the reservoir underwent sequential process of expansion and compression, which resulted in the corresponding changes of porosity and permeability. The different initial geological parameters of the three hydrate layers showed respective coupling characteristics between flow and geomechanics. Additionally, we also analyzed the geological stability of reservoir. The calculation results of horizontal and vertical effective stresses were within the elastic region away from the Mohr-Coulomb yield function until 1800 d. In contrast, the layer with high hydrate saturation was more likely to produce shear failure. Finally, the gas-water production was determined after the coupled flow and geomechanical analysis. The result showed that gas productions of the two horizontal wells were on par, while water production of upper well was >7 times that of lower well. The numerical model and analysis could provide useful insight into the marine heterogeneous hydrate exploitation. Highlights: A multi-layer heterogeneous hydrate model is established. Coupled flow and geomechanical analysis during depressurization is conducted. The possibility of stress failure at different production pressures is analyzed. Water production of upper well is > 7 times higher than that of lower well.